DLSU-Manila bagged the regional and national prizes in the first nationwide search for the most outstanding project undertaken through volunteerism in Higher Education Institution - De La Salle University, Manila (Animo Repository, 1999)
For bringing low-cost and environmental-friendly source of energy to indigenous communities in Abra, DLSU-Manila bagged the regional and national prizes in the first nationwide Search for the Most Outstanding Project Undertaken Through Volunteerism in Higher Education Institution conducted in celebration of National Volunteer Month in December.